1991
DOI: 10.1063/1.348554
|View full text |Cite
|
Sign up to set email alerts
|

Organoarsine pyrolysis mechanisms and their influence on GaAs epilayer purity

Abstract: Thermal decomposition mechanisms have been inferred for a series of organoarsine chemical vapor deposition precursors, and this data has been correlated with the quality of GaAs films grown from these reagents. Tri-, di-, and mono-ethylarsine, as well as a mixture of triethylarsenic and arsine, were pyrolyzed under pseudogrowth conditions, and their decomposition mechanisms were inferred from a qualitative and quantitative analysis of the reaction mixture components. The primary decomposition step for the ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The advent of tert -butyl-substituted compounds paved the way for improved CVD procedures because of their much lower decomposition temperatures. , Typical precursor molecules of this second generation carry larger alkyl ligands like ethyl or tert -butyl, e.g., M­(C 2 H 5 ) 3 (M = B–In) or EH 2 ( t -C 4 H 9 ) (E = P, As). After long-standing discussions in the literature about the relative importance of homolytic dissociation and β-hydrogen elimination channels, the latter was found to be responsible for the low-temperature decomposition characteristics. ,, In a recent computational study, we have shown that β-hydrogen elimination reactions are indeed the kinetically most favorable gas-phase decomposition pathways under CVD conditions for both group 13 and 15 compounds . Thus, an understanding of this mechanism is crucial for further advancement in this research field.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The advent of tert -butyl-substituted compounds paved the way for improved CVD procedures because of their much lower decomposition temperatures. , Typical precursor molecules of this second generation carry larger alkyl ligands like ethyl or tert -butyl, e.g., M­(C 2 H 5 ) 3 (M = B–In) or EH 2 ( t -C 4 H 9 ) (E = P, As). After long-standing discussions in the literature about the relative importance of homolytic dissociation and β-hydrogen elimination channels, the latter was found to be responsible for the low-temperature decomposition characteristics. ,, In a recent computational study, we have shown that β-hydrogen elimination reactions are indeed the kinetically most favorable gas-phase decomposition pathways under CVD conditions for both group 13 and 15 compounds . Thus, an understanding of this mechanism is crucial for further advancement in this research field.…”
Section: Introductionmentioning
confidence: 97%
“…The position of the TSs are set to ζ = 0, and the transition regions are separated from the reactant (educt) and product regions by shaded areas as determined by extrema of the reaction force F(ζ), where κ(ζ)10.1021/acs.inorgchem.5b00687Inorg. Chem.…”
mentioning
confidence: 99%